Fostering Inclusion Through Professional Development: The Case of Faculty Workshops at the University of Rhode Island A Chapter Submitted for: Challenging Higher Education in the 21st Century - Vaccaro, Annamarie (Autonomy and Responsibility Journal of Educational Sciences, 2022)
In the United States, post-secondary institutions have enacted a variety of approaches to foster inclusion of diverse students. Some efforts (e.g., training, workshops) are aimed at teachers, who spend significant time with students, and thus, have a direct influence on whether, and how, students feel included. This study provides rich detail about a series of professional development workshops at one U.S. institution. The goals of the workshops were to increase instructor knowledge of inclusion and to offer tangible strategies for fostering it in their spheres of influence. The manuscript details the history, design, implementation, and selected outcomes of the Inclusion Workshops for Faculty.